Myocardial Infarction After High-Dose Catecholamine Application—A Case Report From an Experimental Imaging Study - Beyhoff, Niklas; Lohr, David; Thiele, Arne; Foryst-Ludwig, Anna; Klopfleisch, Robert; Schreiber, Laura M.; Kintscher, Ulrich (Frontiers in Cardiovascular Medicine, 2020)
Although heart failure following myocardial infarction (MI) represents a major health burden, underlying microstructural and functional changes remain incompletely understood. Here, we report on a case of unexpected MI after treatment with the catecholamine isoproterenol in an experimental imaging study in mice using different state-of-the-art imaging modalities. The decline in cardiac function was documented by ultrahigh-frequency echocardiography and speckle-tracking analyses. Myocardial microstructure was studied ex vivo at a spatial resolution of 100 × 100 × 100 μm3 using diffusion tensor magnetic resonance imaging (DT-MRI) and histopathologic analyses. Two weeks after ISO treatment, the animal showed an apical aneurysm accompanied by reduced radial strain in corresponding segments and impaired global systolic function. DT-MRI revealed a loss of contractile fiber tracts together with a disarray of remaining fibers as corresponding microstructural correlates. This preclinical case report provides valuable insights into pathophysiology and morphologic–functional relations of heart failure following MI using emerging imaging technologies.